2020
DOI: 10.3174/ajnr.a6568
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Rupture Risk in Patients with Unruptured Intracranial Aneurysms Treated with Endovascular Therapy: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Surveillance imaging of previously unruptured, coiled aneurysms remains routine even though reports of rupture of these aneurysms are extremely rare. PURPOSE:We performed meta-analysis to examine long-term rupture risk over $1-year follow-up duration in patients with unruptured intracranial aneurysm who underwent endovascular therapy.DATA SOURCES: Multiple databases were searched for relevant publications between 1995 and 2018.STUDY SELECTION: Studies reporting outcome of long-term rupture risk ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recent studies demonstrated a very low incidence of rebleeding for ruptured aneurysms and bleeding for unruptured aneurysms after coil embolization 48 , 49) along with risk factors for the aneurysm rupture. 48) Although the correlation between bleeding from coiled aneurysms and recanalization has not been well clarified, we believe that aggressive intervention for recanalized aneurysms is one of the reasons for this low rupture rate of coil aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated a very low incidence of rebleeding for ruptured aneurysms and bleeding for unruptured aneurysms after coil embolization 48 , 49) along with risk factors for the aneurysm rupture. 48) Although the correlation between bleeding from coiled aneurysms and recanalization has not been well clarified, we believe that aggressive intervention for recanalized aneurysms is one of the reasons for this low rupture rate of coil aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that while unruptured aneurysms with a remnant after endovascular treatment had a very low risk of rupture (0.6%), ruptured aneurysms had a higher risk of rerupture (3.4%) from a neck remnant. In their systematic review and metaanalysis, given a 5% retreatment rate, Rizvi et al 29 showed that spontaneous rupture of previously unruptured, small-and medium-sized, well-treated aneurysms was exceedingly rare (0.25%) after coiling. However, it should be taken into consideration that the retreatment of aneurysms after endovascular treatment due to the growing residual or recanalization prevents to be faced more reruptured cases.…”
Section: Discussionmentioning
confidence: 99%
“…During a mean follow-up duration of 3.2 years, 12 patients (0.25%) experienced rupture of a UIA after the initial year of treatment resulting in rupture rate of 0.48 (95% CI 0.45-0.51) per 100 patient-years. 74 Two registry based retrospective studies provide data on risk of aneurysm rerupture or intracranial haemorrhage after microsurgical occlusion or endovascular of UIA. A nationwide retrospective cohort study in South Korea used health insurance data for 11,777 patients undergoing surgical clipping and 14,634 patients undergoing endovascular treatment between 2008 through 2014.…”
Section: Additional Informationmentioning
confidence: 99%
“…The systematic review on long-term follow-up after endovascular treatment of UIA found a retreatment rate of 4.9% (95% CI 4.3-5.5), but also noted the lack of systematic nature of follow-up and short duration of follow-up (mean 3.2 years) as limitations of the studies included in the review. 74 In a study using administrative data from all non-federal hospitalisations in California (2005)(2006)(2007)(2008)(2009)(2010)(2011) and Florida (2005-2014) that was published after the data search from the above mentioned systematic review, retreatment rates for UIA patients were 4.6% (95% CI 3.9-5.4) after surgical clipping and 10.6% (95% CI 9.8-11.4) after endovascular occlusion. 33 In the retrospective cohort study from South Korea the probabilities of retreatment at 7 years were 3.2% (95% CI 2.9-3.5) in the surgical clipping group and 4.9% (95% CI 4.6-5.3) in the endovascular coiling group.…”
Section: Additional Informationmentioning
confidence: 99%